Aplikasi Mobile Learning Fisika dengan Menggunakan Adobe Flash sebagai Media Pembelajaran Pendukung - I Made Astra (Jurnal Pendidikan dan Kebudayaan, 2012)
The objective of this research is to create a supporting instructional media in the form of mobile learning of main material for Senior Secondary School students. The created mobile learning was played on mobile phone that supports flash player, mainly Symbian S60 3rd-based mobile phone. The method applied in this research was research and development. The first step was limited on material of heat transfer. The trial of application was conducted to 2 specialized lecturers, 2 media experts, 2 Physics teachers of Senior Secondary School, and 44 students of Diponegoro Senior Secondary School, Jakarta. Indicators used to assess the created instructional media were appropriateness of the content to the purpose, appropriateness of instruction to the technical quality. Marks of the three indicators were above 80%, so that the created mobile learning was categorized as very good. Based on the findings, it may be concluded that the instructional media in the form of mobile learning can be used as a supporting instructional media for Senior Secondary School students to learn Physics subject. ABSTRAKPenelitian ini bertujuan untuk menghasilkan media pembelajaran pendukung berbentuk mobile learning pada materi esensial untuk siswa SMA. Mobile learning yang dibuat dijalankan pada handphone yang mendukung flash player terutama berbasis symbian S60 3rd. Metode yang digunakan dalam penelitian ini, yaitu metode penelitian dan pengembangan (Research and Development). Tahap pertama dibatasi pada materi perpindahan kalor. Uji coba aplikasi dilakukan kepada 2 orang dosen ahli materi dan 2 orang ahli media, dan 2 guru fisika SMA, serta 44 siswa SMA Diponegoro 1 Jakarta. Indikator yang digunakan untuk menilai media pembelajaran yang dibuat, yaitu kesesuaian isi dan tujuan, kesesuaian pembelajaran dan kualitas teknis . Nilai dari ketiga indikator berada di atas 80%, sehingga mobile learning yang dibuat dikategorikan sangat baik. Berdasarkan hasil penelitian, dapat disimpulkan bahwa media pembelajaran berbentuk mobile learning dapat dijadikan sebagai media pembelajaran pendukung pada pelajaran Fisika untuk siswa SMA.